Accelerating Regional Development of the Outer Islands: The Implementation of Special Economic Zones in Indonesia - Siregar, Yani Parasti (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
This case study examines regional development in Indonesia. For decades, economic development efforts by the national government centered on the island of Java, exacerbating unequal development on the other islands, including Sumatra, Kalimantan, Sulawesi, and Papua. To address the issue, the Indonesian government established Special Economic Zones (SEZ, or in Indonesian: Kawasan Ekonomi Khusus, KEK). However, efforts to promote business development within the SEZs faced two challenges: overly complex bureaucracy and lack of basic infrastructure. In response, the government established integrated one-stop service centers to handle all required business actions. In addition, the central and local governments worked together with SEZ operators to build critical infrastructure. As a result, the SEZs were able to provide more job opportunities and economic activities for local people.
Keywords: Social; Urban; Rural and Resilience